Bibliography of emblematic manuscripts - Sider, Sandra, 1949-; Obrist, Barbara (Corpus librorum emblematum., 1997)
Multiple indices provide full access to the manuscript descriptions: topics and genres, titles, artists, translators, dedicatees, additional names, provenance (including dealers and auction houses), dates of production, and places of production. All shelfmarks are listed separately by collection and city, keyed to the entry number for each manuscript. Many entries include notes of iconographic, artistic, or literary interest. A lengthy secondary bibliography completes the volume. Only sixty-eight of these manuscripts have been published and many of the 200 named authors are not normally known as creators of emblematic works. Approximately one third of the manuscripts have never been described in a printed catalogue.